Penatalaksanaan Anestesi Pasien Transposition of the Great Arteries pada Operasi Mouth Preparation - Nugraha, Ade Arya; Suwarman, -; Zulfariansyah, Ardi (Jurnal Anestesi Perioperatif, 2014)
Transposition of the great arteries (TGA) disebabkan kegagalan pemisahan trunkus arteriosus, sehingga aorta keluar dari bagian anterior ventrikel kanan dan arteri pulmonal keluar dari ventrikel kiri. TGA termasuk kelainan jantung bawaan tipe sianotik. Seorang anak perempuan berusia 4 tahun datang untuk perawatan dan pencabutan gigi sebagai persiapan untuk operasi koreksi TGA di Rumah Sakit Dr. Hasan Sadikin Bandung pada Januari 2014. Anamnesis didapatkan riwayat kebiruan sejak bayi dan pada pemeriksaan fisis didapatkan anak yang tampak sianosis, SpO2 70â80%, murmur sistol, dan jari tabuh. Pada pemeriksaan ekokardiografi didapatkan kelainan TGA. Manajemen anestesi pada pasien ini dilakukan dengan menggunakan ketamin dan vekuronium untuk induksi serta pemeliharaan dengan O2 dan air, serta sevofluran. Manajemen anestesi dilakukan dengan target mencegah penurunan miring systemic vascular resistance (SVR) dibandingkan dengan pulmonary vascular resistance (PVR). Simpulan, prinsip pengelolaan perioperatif pembedahan nonkardiak pada pasien TGA adalah menjaga agar tidak terjadi penurunan SVR dan peningkatan PVR.Kata kunci: Kelainan jantung kongenital sianotik, pulmonary vascular resistance (PVR), systemic vascular resistance (SVR), transposition of the great arteries (TGA)Management of Anesthesia in Patients Transposition of the Great Arteries which Undergo Mouth PreparationTransposition of the great arteries (TGA) results from failure of the truncus arteriosus to spiral, so that the aorta arises from the anterior portion of the right ventricle and the pulmonary artery arises from the left ventricle. TGA which is the type of cyanotic congenital heart disease. A girl of 4 years came for treatment and tooth extraction as preparation for the surgical correction ofÂ  TGA at the Dr. Hasan Sadikin Hospital âBandung within January 2014. Patient with a history of blue when she was a baby and on physical examination found the child looking cyanosis, SpO2 70â80%, sistolic murmur and clubbing finger. Abnormalities on echocardiography obtained TGA.Â  Anesthetic management of this patients was performed using ketamine and vecuronium for induction and maintenance with O2, N2O, and sevoflurane. Cyanotic attacks can occur preoperative, intraoperative, and post operative, which was treated by increasing systemic vascular resistance (SVR) compared to pulmonary vascular resistance. In conclusions, perioperative management principal for non cardiac surgery on transposition of the great arteries (TGA) is to keep SVR from decline andÂ  increase on PVR.Key words: Cyanotic congenital heart defects, pulmonary vascular resistance (PVR), systemic vascular resistance (SVR), transposition of the great arteries (TGA) âÂ DOI: 10.15851/jap.v2n2.320